Determining the Oral Construct of the Test of English Communication Skills - Attan, Anie; Abdul Raof, Abdul Halim; Yusof, Masdinah Alauyah Md; Omar, Noor Abidah Mohd.; Hamzah, Masputeriah (International Journal of Economics and Financial Issues, 2015)
Exit tests to measure and inform new graduates of their oral and written communicative abilities are non-existent. This paper is our attempt to determine the oral construct of the exit test through a study involving graduating students and workplace professionals. Information regarding oral tasks, minimum standards and quality expected from new graduate employees were gathered through interviews and discussions with the human resource personnel from various industries. Based on the information gathered, a pilot test of group oral interaction was designed and administered to a group of four graduating students. The interactions of the group were video-recorded and were then assessed by professionals from various specialisations based on their respective criteria of assessment. The professionals’ responses, comments and suggestions to interview questions posed were noted. The results were analysed to establish the different categories of criteria being applied by the professionals in their assessment of the new graduates’ performances. Findings show that thinking ability, interactive ability and professional image, which go beyond language skills, were other equally important criteria of assessment, besides language accuracy. From the analysis, the construct of oral communication ability for the exit test was determined, followed by the development of a six-band oral rating scale. Keywords: Oral Contruct; Exit Test; Minimum Standard Expected; Workplace Assessment Criteria; Oral Communication Ability JEL Classifications: M000